Self-Care dan Coping Stress pada Working Mothers - Fauziah, Firdha Novia; Rizqi Amalia Aprianty; Ghea Amalia Arpandy (Psikodinamika: Jurnal Literasi Psikologi, 2024)
Abstract Today's women are able to have dual roles in life, being housewives and working mothers. The experiences that working mothers experience in carrying out their work at home and at work cause stress which has an impact on their well-being. Low ability to cope with stress can result in prolonged stress which causes fatigue or burnout. The aim of this research is to determine the relationship between self-care and coping with stress in working mothers. The approach used in this research is quantitative with a correlational design. The scale used is the coping stress variable scale, Ways of Coping of Stress created by Lazarus and Folkman (1986) which has been adapted by Fidia Oktarisa and Zulmi Yusra (2017), and the self-care scale namely Exersice of Self-Care Agency which was produced by Kearney and Fleischer (1979). The number of samples used was 100 respondents with the criteria being working mothers and having at least two children. The results of the analysis show that there is a positive relationship between self-care and coping with stress in working mothers. This shows that the higher the self-care, the higher the stress coping for working mothers. Keywords: coping stress, self-care, working mothers